Financial feasibility of converting plastic waste as an alternative energy source - Askar; Suriani, Seri; Saleh, Haeruddin; Yunus, Kaffrawi; Rasyidi, Emil Salim (Asian Economic and Financial Review, 2025)
The increasing accumulation of non-degradable plastic waste is threatening our environment. Transforming plastic waste into fuel via pyrolysis is a promising approach. This research aims to evaluate the economic viability of a project that converts plastic waste into gasoline, diesel, and kerosene through the pyrolysis process. The profit and loss projection, Net Present Value (NPV), Internal Rate of Return (IRR), Return on Investment (ROI), Break-Even Point (BEP), and Contribution Margin (CM) were calculated over 10 years to conduct the analysis. The analysis indicates that the project demonstrates significant financial viability, featuring an NPV of IDR 550.75 billion, an estimated IRR exceeding 1000%, an ROI of 1,610.7%, a BEP of around 23 working days, and a CM of IDR 7,040 per liter or 86.9%. However, this research has some limitations, including the quality of the generated products, the environmental implications of the pyrolysis process, and the reliable supply of raw materials. This research provides a more comprehensive understanding of the feasibility of the plastic waste-to-fuel conversion project from a technical and financial perspective by incorporating a comprehensive technical and financial analysis. It also supports the concepts of a circular economy and sustainable waste management by turning waste into a valuable resource.